Memetic performance and participatory spectacle: audience ritual in the 2025 Minecraft movie - Madsen, Dag Øivind (Frontiers in Communication, 2025)
In 2025, the release of the Minecraft movie triggered a wave of youth-driven audience participation centered on the meme reference “chicken jockey,” which escalated into viral, in-theater performances. This paper examines the event as a case of memetic performance, where digital cultural scripts shape real-world behavior. Drawing on media ritual theory, participatory culture, and platform studies, the analysis explores how symbolic fluency and algorithmic amplification transform spectatorship into collective ritual. Using an interpretive case study approach based on secondary sources, the study situates the “chicken jockey” chant within a broader shift toward participatory spectacle. While focused on a single, culturally specific case, the paper offers conceptual insights into how memes function as both communicative codes and ritual cues, blurring boundaries between online signaling and offline performance in a platform-mediated media environment.